Assessing surface air pressure sensing using 118 GHz O2-absorption radar system. (March 2021) - Lin, Bing; Min, Qilong; Hu, Yongxiang
Highlights: Novel approach for surface air pressure remote sensing to fill the observational gap. Significant improvement for sever weather especially hurricane predictions. Using high frequency channels at 118 GHz O2-absorption line to measure surface pressure. Optimized system design for both frequency selections and power distributions. Abstract: This study assesses surface air pressure remote sensing using a differential absorption radar at the 118 GHz O2 line. The considered system would have, at least two, closely-spaced frequency channels. Environmental impacts like surface reflections and absorptions from water vapor and other gases, and liquid water clouds on the radar signals of these channels are very similar, but the difference in O2 absorption is substantial. The surface pressure could be retrieved from the radar measured differential absorption optical depth of the atmosphere. The operational frequencies of the radar system are optimally selected, and the transmitted powers of the paired stronger and weaker O2 absorption channels are carefully distributed to balance the signal-to-noise ratios of these channels. Simulations of radar signals and pressure retrievals show that with an airborne system cruising at 10 km altitude, surface pressure measurements could achieve 1 mb accuracy within 1-s data processing. These pressure measurements would provide urgently needed supports in improving severe and general weather forecasts and gain unique knowledge on planetary boundary layer meteorology. Other advantages of this kind of high frequency radars would be their higher spatial resolution and increased potentials of small- or CubeSat applications.